2020
DOI: 10.1136/tsaco-2020-000502
|View full text |Cite
|
Sign up to set email alerts
|

Damage control hip disarticulation: two-stage operation with index creation of a large medial flap for the septic hip

Abstract: BackgroundAlthough rarely performed, hip disarticulation (HD) is usually used for the patient with a non-viable leg who is also in extremis. HD was first used for trauma and infection; however, the technique was perfected during the age of hindquarter amputation for osteosarcomas. The operation performed by most surgeons today is still based on the oncological principles of high vessel control and ligation. When this approach has been used in the overwhelmingly infected or mangled extremity, it has resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…In most studies, hip disarticulation is indicated as a last resort for infection source control of severe lower extremity infection, such as extensive proximal femoral osteomyelitis, pyoarthritis of hip joint, and severe necrotizing soft tissue infection with hip joint involvement. 8,11,[13][14][15] On the other hand, one case series reported that hip disarticulation with femur removal is performed when the flap size is not sufficient enough for tension-free coverage of the femoral stump. 8 Given our patient's history, we performed the left hip disarticulation and left femur removal in this patient for infection source control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, hip disarticulation is indicated as a last resort for infection source control of severe lower extremity infection, such as extensive proximal femoral osteomyelitis, pyoarthritis of hip joint, and severe necrotizing soft tissue infection with hip joint involvement. 8,11,[13][14][15] On the other hand, one case series reported that hip disarticulation with femur removal is performed when the flap size is not sufficient enough for tension-free coverage of the femoral stump. 8 Given our patient's history, we performed the left hip disarticulation and left femur removal in this patient for infection source control.…”
Section: Discussionmentioning
confidence: 99%
“…Given our patient's history, we performed the left hip disarticulation and left femur removal in this patient for infection source control. However, the literature discussing hip disarticulation in SCI patients with recurrent pelvic injuries are case reports and case series, and the evidence is limited 8,11,13–15 . Further studies are needed to determine the indication of hip disarticulation, and this procedure should be considered depending on patients' clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Veličina režnja kao i temeljna postoperativna nega rane su od velikog značaja za pravilnu dezartikulaciju kuka [14]. Određeni radovi navode starost pacijenta od preko 65 godina i slabije imovinsko stanje kao moguće prediktore za razvoj komplikacija [15].…”
Section: Discussionunclassified
“…Flap size and thorough postoperative wound care are of high importance for proper hip disarticulation [14]. Certain papers note patient age of over 65 years and a lower economic status as possible predictors for the development of complications [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, a cirurgia de controle de danos caracteriza-se como um importante avanço no controle da morbimortalidade dos pacientes graves e politraumatizados 3,4 . Entretanto, a falta de protocolos específicos para a sua indicação a torna um importante desafio nos hospitais de todo o Brasil, valorizando-se então a experiência clínica e a capacidade de decisão do cirurgião 1,5,6 .…”
Section: Introductionunclassified